2009
DOI: 10.1007/s00011-008-8226-z
|View full text |Cite
|
Sign up to set email alerts
|

Tumor bearing decreases systemic acute inflammation in rats – role of mast cell degranulation

Abstract: Tumor bearing can limit mast cell function and vascular events in acute systemic inflammation in rats, without changes in neutrophil migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…These results suggest that the anti-edematogenic response of SP-Gb is complex and may be related to the inhibition of both neutrophil migration and the release of vasoactive amines. This is probably a result of the anti-histaminic effect that may be caused by the inhibition of mast cell degranulation [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the anti-edematogenic response of SP-Gb is complex and may be related to the inhibition of both neutrophil migration and the release of vasoactive amines. This is probably a result of the anti-histaminic effect that may be caused by the inhibition of mast cell degranulation [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that 15 days after tumor inoculation, animal mortality reached 100% (3). Thus, in this study, we evaluated the effects of tumor bearing on the 4th and 7th day after tumor inoculation.…”
Section: Methodsmentioning
confidence: 60%
“…Recently, our group demonstrated that Walker tumor bearing can limit mast cell function and vascular events in acute systemic inflammation models in rats, without changes in neutrophil migration (3). In the present study, our results demonstrate that Walker tumor bearing produced a peripheral antinociceptive effect in PGE 2 - or carrageenan-induced mechanical hypernociception, and this effect was mediated at least in part by activation of the NO/cGMP pathway, followed by the opening of KATP channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies involving implication of ascorbic acid in the modulation of antitumor effects or toxicities induced by various anticancer drugs have been done separately in cancer cell lines/tumors in vivo or in normal animals, respectively. Since cancers may alter the metabolic and endocrine equilibrium in the host (Barbosa et al, 2009), it is reasonable that the ascorbic acid-mediated protective strategies on cisplatin-induced mutagenic effects should be tested in tumor-bearing hosts which may also propose that inspective protective agents are useful in enhancing therapeutic efficacy. Our recent studies have shown that the combination treatment using ascorbic acid with cisplatin show better antitumor activity and reduced tissue toxicities in the hosts (Amenla et al, 2013;Longchar and Prasad, 2015).…”
Section: Introductionmentioning
confidence: 99%